DISIPLIN KERJA PEGAWAI DINAS PENDIDIKAN KOTA PADANG - Rosi Haryani (Universitas Negeri Padang, 2013)
The research is based on the phenomenon that shows discipline employees who work less well. This study aimed to obtain information about the discipline desert city education office employees. This is a descriptive study reasearch. The population in this study were all employees of the Department of Education Padang, totaling 95 people. Samples taken were 76 people. Data collection tool used was a questionnaire Likert scale models. This questionnaire has been tested for validity and reliabelity. Data were analyzed with an average score formula. The results showed that: (1) according to the discipline of the employees working on the timeliness aspect categories with an average score of 3.9. (2) employee disciplinary aspects of consciousness are the categories with a mean score of 3.8, and (3) employee discipline aspect of compliance is in good category with an average score of 3.6 In general discipline of employee services educational desert town located in both categories with an average score overall was 3.8. Keywords : Employee Discipline